Exploring Legal Protections for Platform Workers in Malaysia: A Human Rights-Based Perspective - Makhtar, Maheran; Abd Ghadas, Zuhairah Ariff; Haque, Mahbubul (Faculty of Law, Universitas Padjadjaran, 2024)
Platform work has gained significant recognition due to the rapid growth of the digital economy, which offers new opportunities for workers. However, inadequate regulatory frameworks in Malaysia have led to various human rights concerns, particularly regarding the protection of workers' rights, such as social security, fair remuneration and safe working conditions. Furthermore, the challenge of providing worker protections must be balanced with the flexible nature of the gig economy. Thus, this study explored the evolving legal landscape surrounding the protection of platform workers’ rights in Malaysia from both legal and human rights perspectives. It examines the role of business and human rights in finding the delicate balance between economic progress and protecting workers’ fundamental rights, emphasizing the role of regulation. This study adopts a qualitative approach through review of existing literature, including academic research, reports, and relevant legal documents, to provide a comprehensive understanding of the issue. Therefore, this study underscores the urgent need for robust legal frameworks and regulatory measures to safeguard the rights and welfare of platform workers in Malaysia through the integration of corporate responsibility to respect human rights and to establish mechanisms that guarantee fair remuneration, job security, social protection, and avenues for workers’ representation and collective bargaining. The findings of this study are expected to contribute to the growing body of literature on platform work and serve as a basis for policy recommendations and advocacy efforts to improve the rights and working conditions of platform workers in Malaysia.